Морфологічні особливості плодів та насіння і насіннєва продуктивність деяких видів Hosta Tratt. у дендропарку “Софіївка” - Ivankovska, I.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The results of the biomorphological features of the fruits and seeds of some species Hosta Tratt. from the collection of the National Dendrological Park Sofiyivka of the NAS of Ukraine are presented. The main data of seed productivity are given.